Studi Pendahuluan Komparasi Kapasitas Produksi Pada UKM Batu Bata Berbasis Family Business - Fauzan Romadlon; Alya Farahdina Alfiani; Nuansa Aita Putri; Wahyu Bagas Laksana (Universitas Bunda Mulia, 2021)
This preliminary study aims to compare production capacity at the family business of bricks at Sokaraja District, Banyumas Regency. The majority of the businesses are done traditionally with family business managerial-based norms. The method used is the cost estimation analysis and the Analysis of Variance (ANOVA) method to calculate the statistical significance of production among SMEs. In addition, based on statistical analysis there are significant differences among the three bricks SMEs for production capacity. The implications of these calculations can be used as an initial step to consider in general determining the logistics conditions, sales strategies, and the role of succession in the family business. In practice, increasing production capacity, reducing production costs, and product innovation can be achieved if the involvement of family members were optimal to ensure and enhance the business’s sustainability.